2016
DOI: 10.1002/ece3.2074
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and growth reduction with warming are driven by nonstomatal limitations in a Mediterranean semi‐arid shrub

Abstract: Whereas warming enhances plant nutrient status and photosynthesis in most terrestrial ecosystems, dryland vegetation is vulnerable to the likely increases in evapotranspiration and reductions in soil moisture caused by elevated temperatures. Any warming‐induced declines in plant primary production and cover in drylands would increase erosion, land degradation, and desertification. We conducted a four‐year manipulative experiment in a semi‐arid Mediterranean ecosystem to evaluate the impacts of a ~2°C warming o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 80 publications
6
38
0
1
Order By: Relevance
“…Despite these variable effects of warming on leaf nutrient concentrations, we found an overall decrease in mature leaf nutrient contents (i.e., leaf N, P, K, Ca, Mg, S, Fe, and Zn pools) with warming, either alone (W) or in combination with rainfall reduction (W+RR). This is in contrast to other studies that found minor, neutral, or even positive effects of climate change on leaf nutrients in temperate and boreal ecosystems (Aerts et al, ; Bai et al, ; Chapin, Shaver, Giblin, Nadelhoffer, & Laundre, ; Hobbie & Chapin III, ; Welker, Fahnestock, Sullivan, & Chimner, ; Zong et al, ), but is consistent with previous observations in dry Mediterranean ecosystems (León‐Sánchez et al, , , ; Salazar‐Tortosa et al, ; Sardans et al, ; Sardans, Peñuelas, et al, ; Sardans, Peñuuelas, Estiarte, & Prieto, ).…”
Section: Discussionsupporting
confidence: 91%
“…Despite these variable effects of warming on leaf nutrient concentrations, we found an overall decrease in mature leaf nutrient contents (i.e., leaf N, P, K, Ca, Mg, S, Fe, and Zn pools) with warming, either alone (W) or in combination with rainfall reduction (W+RR). This is in contrast to other studies that found minor, neutral, or even positive effects of climate change on leaf nutrients in temperate and boreal ecosystems (Aerts et al, ; Bai et al, ; Chapin, Shaver, Giblin, Nadelhoffer, & Laundre, ; Hobbie & Chapin III, ; Welker, Fahnestock, Sullivan, & Chimner, ; Zong et al, ), but is consistent with previous observations in dry Mediterranean ecosystems (León‐Sánchez et al, , , ; Salazar‐Tortosa et al, ; Sardans et al, ; Sardans, Peñuelas, et al, ; Sardans, Peñuuelas, Estiarte, & Prieto, ).…”
Section: Discussionsupporting
confidence: 91%
“…Warming of a semi‐arid shrubland also caused a reduction of A net , with no accompanying decline in g s , reducing leaf WUE (León‐Sánchez et al . ). The change in leaf level WUE we observed with warming has significant implications for our understanding of how dryland water and C cycles, and their interactions, will respond to global change.…”
Section: Discussionmentioning
confidence: 97%
“…; León‐Sánchez et al. ). Consequently, they have different mechanisms to adjust their transpiring biomass during summer.…”
Section: Discussionmentioning
confidence: 98%
“…; León‐Sánchez et al. ). Gypsum crystallization water seems a relatively stable water source for shallow‐rooted plants, but it may come at a cost.…”
Section: Discussionmentioning
confidence: 98%